Walking Ability Is a Major Contributor to Fear of Falling in People with Parkinson's Disease: Implications for Rehabilitation - Nilsson, Maria H. (Hindawi Publishing Corporation, 2012)
Although fear of falling (FOF) is common in people with Parkinson's disease (PD), there is a lack of research investigating potential predictors of FOF. This study explored the impact of motor, nonmotor, and demographic factors as well as complications of drug therapy on FOF among people with PD. Postal survey data (including the Falls Efficacy Scale, FES) from 154 nondemented people with PD were analyzed using multiple regression analyses. Five significant independent variables were identified explaining 74% of the variance in FES scores. The strongest contributing factor to FOF was walking difficulties (explaining 68%), followed by fatigue, turning hesitations, need for help in daily activities, and motor fluctuations. Exploring specific aspects of walking identified three significant variables explaining 59% of FOF: balance problems, limited ability to climb stairs, and turning hesitations. These results have implications for rehabilitation clinicians and suggest that walking ability is the primary target in order to reduce FOF. Specifically, balance, climbing stairs, and turning seem to be of particular importance.